2022
DOI: 10.3389/fpsyt.2022.904426
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cognitive Impairment in Depression. May Probiotics Help?

Abstract: Depression is the major cause of disability globally. Apart from lowered mood and accompanying symptoms, it leads to cognitive impairment that altogether predicts disadvantaged social functioning. Reduced cognitive function in depression appears a bit neglected in the field of clinical and molecular psychiatry, while it is estimated to occur in two-thirds of depressed patients and persist in at least one third of remitted patients. This problem, therefore, requires elucidation at the biomolecular and system le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…A recent population-based study of middle-aged adults demonstrated that microbial community composition on the basis of beta-diversity was associated with all cognitive measures in multivariable-adjusted analysis [ 128 ], suggesting a role of gut microbiota in cognitive decline with aging. It has also been suggested that dysbiosis of gut microbiota may play a role in cognitive impairment in patients with psychiatric disorders such as schizophrenia, MDD, and BD [ 128 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent population-based study of middle-aged adults demonstrated that microbial community composition on the basis of beta-diversity was associated with all cognitive measures in multivariable-adjusted analysis [ 128 ], suggesting a role of gut microbiota in cognitive decline with aging. It has also been suggested that dysbiosis of gut microbiota may play a role in cognitive impairment in patients with psychiatric disorders such as schizophrenia, MDD, and BD [ 128 132 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between mood and cognition in depressed individuals without a comorbid neurologic disorder is well documented. Depressed individuals are more likely to have impaired cognitive speed, memory, naming ability, planning, and problem-solving compared to non-depressed individuals [ 29 ]. The association between depression and cognitive difficulties in individuals with PSD is thought to reflect the effect of co-occurring brain damage (hippocampal damage leads to forgetfulness and emotion-regulation difficulties) or changes in environment (sadness with reduced opportunities leading to trouble with attention and forgetfulness) [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics play a crucial role in reducing oxidative stress by producing various antioxidant enzymes (catalase and superoxide dismutase), antioxidants (butyrate, folate, and glutathione), and chelating metal ions. Probiotics may prevent immune actions like inflammatory responses by inhibiting TLR activation ( Dobielska et al, 2022 ). The reduced inflammatory state could enhance the blood-brain barrier integrity and improve neurological functions ( Wang et al, 2023 ).…”
Section: Mechanisms Underlying Probiotic Effects On the Gut-brain Axismentioning
confidence: 99%